Al-Quran dan Semantik Toshihiko Izutsu - Siti Fahimah (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
In understanding the Koran, there are many approaches that can be applied, including by using the semantic approach proposed by Thoshihiko Izutsu. One of the cases raised by Tashihiko's semantic approach is to understand the concept of maqam, the choice of using semantics in understanding the Koran will result in a comprehensive understanding other than what is done by conventional tafsir scholars. The steps taken in Tashihiko's semantic are searching for keywords, looking for basic meanings and relational meanings which include syntagmatic and diachronic analyzes, looking for synchronic and diachronic meanings which include 3 periods, namely, pre-qur'anic, qur'anic and post-qur'anic. , and determine weltanschoung. With these steps, it is found that the word maqam has several results, namely (1) The word maqam and its revasion is mentioned 18 times in the Koran with 7 invented words, namely, مَقَام, مَقَامِي, مَقَامِكَ, مَقَامَهُمَا, مُقاَمَ|, مُقاَمًا, and المُقاَمَةِ. What is contained in 16 letters, namely, 1) QS. Al-Baqarah, 2) QS. Ali Imran, 3) QS. Al-Maidah, 4) QS. Yunus, 5) QS. Ibrahim, 6) QS. Al-Isra ', 7) QS. Maryam, 8) QS. Al-Furqan, 9) QS. As-syu'arah, 10) QS. An-Naml, 11) QS. Al-Ahzab, 12) QS. Fathir, 13) QS. As-Shaffat, 14) QS. Ad-Dukhan, 15) QS. Ar-Rahman, and 16) QS. An-Naziat. (2) Weltanschauung said maqa m is: 1) Maqa m means al-wa'du wa al-wa'id, 2) Maqam means al-hijr, and 3) Allah means the holder of prerogative rights.